Brain gym therapy for children - Dina Indrati D Sulistyowati; Remilda Armika Vianti; Nur Azizah (Proceedings Series on Health & Medical Sciences, 2020)
Child and adult health risks including obesity, hypertension and diabetes may be programmed by nutrional status during this period.. Approximately 5 to 10% of children are estimated to have developmental delays. Therefore, the need for stimulation so that soft motorik development in children to improve optimally. Therapy for brain gymnastics can be stimulated for to improving the soft motorik development of children.The purpose of this study was to determine the effect of brain gymnastics therapy on the development of soft motorik in 4-6 years of age.This research method is quasy experimental with non-randomized control group pretest-posttest design. With purposive sample. 42 respondents were divided into the control group and the intervention group. Soft motorik development of children before and after being given treatment by using gymnastics therapy of brain has increased 76.2 % with significantly p value 0.045 (<0.05). In conclusion the gift of brain gymnastics therapy can improve the motor development of children aged 4-6 years. Suggestions for schools, parents can provide premature stimulation by providing a brain gymnastics game that can stimulate child development.